2012
DOI: 10.1152/ajpendo.00192.2011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal age and growth on placental nutrient transport: potential mechanisms for teenagers' predisposition to small-for-gestational-age birth?

Abstract: Teenagers have an increased risk of delivering small-for-gestational-age (SGA) infants. Young maternal age and continued skeletal growth have been implicated as causal factors. In growing adolescent sheep, impaired placental development and nutrient transfer cause reduced birth weight. In human pregnancies, SGA is associated with reduced placental amino acid transport. Maternal growth has no effect on placental morphology or cell turnover, but growing teenagers have higher birth weight:placental weight ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 55 publications
(72 reference statements)
5
36
0
1
Order By: Relevance
“…However, the activity of system A transporters was higher in placentas from growing compared with nongrowing teenagers. 77 These observations are broadly in line with an earlier study demonstrating that the villous/capillary surface area in placentas from adolescent mothers does not correlate with either maternal chronological age or bone age. However, this study did find an inverse correlation between the placental villous/capillary surface and gynecological age, further suggesting that uterine immaturity is the primary driver of placental dysfunction during adolescence.…”
Section: Placental Studiessupporting
confidence: 91%
“…However, the activity of system A transporters was higher in placentas from growing compared with nongrowing teenagers. 77 These observations are broadly in line with an earlier study demonstrating that the villous/capillary surface area in placentas from adolescent mothers does not correlate with either maternal chronological age or bone age. However, this study did find an inverse correlation between the placental villous/capillary surface and gynecological age, further suggesting that uterine immaturity is the primary driver of placental dysfunction during adolescence.…”
Section: Placental Studiessupporting
confidence: 91%
“…To date, there is limited data on the precise nutritional needs of adolescents during pregnancy and lactation, but the increased risk of preterm delivery and low birth weight has been correlated to alterations of placental function in pregnant adolescents [90,91]. It has been shown that, in addition to biological immaturity, the inadequate nutritional status (e.g., breakfast skipping, improper weight loss diet, energy-dense foods) could play important roles in the onset of complications in the perinatal period [92].…”
Section: Focus On Conditions Associated With Nutrient Deficienciesmentioning
confidence: 99%
“…A nested case–control study was utilized for placental analyses, with low and adequate folate status cohorts selected to match most closely on demographic and biophysical characteristics. Sample sizes were dictated by power calculations based on previous studies .…”
Section: Methodsmentioning
confidence: 99%
“…Sodium‐dependent uptake of 14 C‐methylaminoisobutyric acid (PerkinElmer, Buckinghamshire, UK) was measured to assess amino acid transporter system A activity in placental fragments as described . The rate of uptake over 10–30 min was calculated and normalized for fragment protein content.…”
Section: Methodsmentioning
confidence: 99%